Classroom Management in Learning Islamic Education in Class 7 SMPN 1 Cikarang Utara - Rafika Zahra Mulyana; Lilis Karyawati; Nia Karnia (CV. Rayyan Dwi Bharata, 2023)
Classroom management is a picture carried out by the person in charge of teaching and learning activities who share with the aim of achieving idealistic conditions so that good and correct teaching and learning activities are carried out. This research method uses qualitative methods with in-depth interview methods. The results of the study showed that the combined classroom management approach, namely the teaching approach and the socio-emotional approach, has been effective in classroom management in PAI class 7 SMPN 1 Cikarang Utara. Judging from the arrangement of the classroom, anticipating class conditions, setting rules in the classroom, the teacher ensures that students remain focused, serious but relaxed, enthusiastic in learning activities. And the obstacles faced are the activeness of students when in class, the diverse understanding of students in receiving the material presented and students in collecting assignments given by the teacher. Then the solution to these obstacles is that the teacher must know each student's understanding ability in receiving material, always evaluate student learning outcomes, give assignments by adjusting students' understanding abilities, the teacher must be more interactive in class so that students can also be active in class, but those obstacles it must be enjoyed and we accept it with an open heart and we as teachers must know how to overcome these problems.